Technological Pedagogical Content Knowledge (TPACK) Approach In Arabic Language Learning At Madrasah Miftahul Afkar - Fuad Hasim, Muhamad; Thohir, Muhammad; Baihaqi, M.; Iqbal Fuadhi, Muhammad; Islamiyah, Nur (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
The development of science and ICT (information, communication, & technology) requires teachers as the main component of the learning process to be able to integrate technology into the learning process. TPACK is a learning approach that integrates technology, pedagogy, and subject matter into learning. The use of technology in Arabic language learning, one of the goals of which is to master four language skills (maharatul istima', maharatul kalam, maharatul qiraah, and maharah kitabah), is very helpful in achieving the expected competencies both as a learning resource and as a learning media. This study aims to examine the implementation of TPACK-based Arabic language learning and its use at Madrasah Miftahul Afkar Kediri based on source searches (documentation and teachers and learning media) that are then classified and processed, interpreted, and concluded. This research employs a qualitative approach, proceeding through several stages. Initially, the researcher gathers various documents and data pertinent to TPACK. Second, the researcher observes the research object (Madrasah Miftahul Afkar, Kediri). Third, the researcher analyzes and draws conclusions from the obtained and collected documents and data. Based on the results of this study, it can be concluded that Arabic language teachers at Madrasah Miftahul Afkar have implemented TPACK, which combines technology, pedagogy, and content in learning Arabic through the learning and teaching process.